Símbolo, mito y rito: el cuerpo y la sangre - Castillo, Ignacio (ITER / Instituto de Teología para Religiosos, 2006)
We will approach the communicative structure of the symbol, its rhetorical turn and its ambiguity, through its mythical and ritual expressions. The myth is a human way of establishing ultimate senses. It helps to approach the question of human existence, and its ambiguity is opposed to the possibility of an objective truth. A ritual expression is a performance of the symbolic power and the mythical event. Its ambiguity will always represent the risk of replacing life experience. Through this forms, we will make a phenomenological reading of the body and the blood as mythical-symbolic-ritual forms present in many ethnic traditions.